Renal Histological Effects of Artificial Sweeteners in Albino Rats (International Journal of Environmental Sciences, 2025)
The study was conducted to evaluate the effect of different doses of artificial sweeteners on the kidneys of male and female rats, and to identify the potential renal tissue damage effects. The study included (15) male and female rats that were subjected to the necessary laboratory conditions for 30 days. They were divided as follows: a control group; a group that was given one sweetener tablet dissolved in 2 cc of water at a rate of two doses of 1 cc for a month; and a group that was given two sweetener tablets dissolved in 4 cc of water at a rate of four doses of 1 cc for a month. Histological examination of the kidneys of rats treated with one and two sweeteners revealed tissue lesions in the cortex, fragmentation and atrophy of the glomerulus, expansion of the capsular or urinary space, desquamation of the epithelium lining the parietal layer of Bowman's capsule, and desquamation of the epithelial cells lining several urinary tubules. Hematomas were also present in some sections. The medulla also showed extensive hemorrhage around the urinary tubules and partial desquamation of the epithelium lining several urinary tubules. Our study concluded that the use of sweeteners containing sodium cyclamate and sodium saccharin is unsafe for the kidney and may cause renal tissue lesions over the long term.